(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
This study aims to develop educational game media with a contextual approach assisted by Adobe Animate on feasible and practical algebraic material. The type of research used is Research and Development (R&D) with the ADDIE development model which consists of five stages namely Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 28 students from class VII-F of SMP NU 06 Kedungsuren. The data collection instrument used a media validation questionnaire sheet, a material expert validation questionnaire sheet and a student response questionnaire sheet. The data analysis technique used is descriptive quantitative. The results of this study are in the form of educational game media products with a contextual approach assisted by Adobe Animate on feasible and practical algebraic material. This is based on the percentage of media expert and material expert validation questionnaires of 90.22% and 90.79% with very good criteria and the percentage of student response questionnaires is 86.64% with very good criteria.